Comparison of three different fluid warming techniques used to maintain euthermia in patients who underwent cesarean section - A retrospective audit - Saurabh Sud; Deepak Dwivedi; Sadhan Sawhney; Jagdeep S Bhatia; Josemine Davis; Puja Dudeja (Wolters Kluwer Medknow Publications, 2019)
Context: Intraoperative hypothermia is a leading cause of morbidity in the perioperative period. This retrospective audit study was planned to assess the efficacy of three different active warming devices used in maintaining euthermia in patients who underwent lower segment cesarean section (LSCS). Aims: Audit of the three different fluid warming techniques in maintaining euthermia in patients who underwent cesarean sections. Settings and Design: A retrospective audit. Materials and Methods: In total, 698 patients were included in the study who underwent LSCS and were divided on the basis of the warming technique used into Group 1 (n = 241, blood warming bath), Group 2 (n = 238, cabinet), and Group 3 (n = 219, inline warmer). The preoperative core body temperature was compared in each group with the intraoperative body temperature as well as with core body temperature measured 20 minutes after shifting the patient in the postoperative room as per the entries made in the central anesthesia registry. The incidence of the shivering was also noted from the data for each group separately. Statistical Analysis Used: One-way analysis of variance was applied for comparing the mean (SD) between the three groups and unpaired t-test was used to compare two mean (SD) values.P value <0.05 was considered significant. Results: Comparison of preoperative core body temperature (T0) with intraoperative (T1, T2) and postoperative (T3) temperatures within the groups showed significant results in Group 1 (blood warming bath), demonstrating its inefficiency in maintaining euthermia in the perioperative period. Conclusions: Cabinet and inline fluid warmer prove to be efficacious in maintaining euthermia and limiting shivering in the patients for cesarean section.